The Barrow Neurological Institute Grading Scale as a Predictor for Delayed Cerebral Ischemia and Outcome After Aneurysmal Subarachnoid Hemorrhage: Data From a Nationwide Patient Registry (Swiss SOS). Issue 6 (17th January 2018) - Neidert, Marian Christoph; Maldaner, Nicolai; Stienen, Martin Nikolaus; Roethlisberger, Michel; Zumofen, Daniel W; D'Alonzo, Donato; Marbacher, Serge; Maduri, Rodolfo; Hostettler, Isabel Charlotte; Schatlo, Bawarjan; Schneider, Michel M; Seule, Martin A; et al.
Abstract: BACKGROUND: The Barrow Neurological Institute (BNI) scale is a novel quantitative scale measuring maximal subarachnoid hemorrhage (SAH) thickness to predict delayed cerebral ischemia (DCI). This scale could replace the Fisher score, which was traditionally used for DCI prediction. OBJECTIVE: To validate the BNI scale. METHODS: All patient data were obtained from the prospective aneurysmal SAH multicenter registry. In 1321 patients, demographic data, BNI scale, DCI, and modified Rankin Scale (mRS) score up to the 1-yr follow-up (1FU) were available for descriptive and univariate statistics. Outcome was dichotomized in favorable (mRS 0-2) and unfavorable (mRS 3-6). Odds ratios (OR) for DCI of Fisher 3 patients (n = 1115, 84%) compared to a control cohort of Fisher grade 1, 2, and 4 patients (n = 206, 16%) were calculated for each BNI grade separately. RESULTS: Overall, 409 patients (31%) developed DCI with a high DCI rate in the Fisher 3 cohort (34%). With regard to the BNI scale, DCI rates went up progressively from 26% (BNI 2) to 38% (BNI 5) and corresponding OR for DCI increased from 1.9 (1.0-3.5, 95% confidence interval) to 3.4 (2.1-5.3), respectively. BNI grade 5 patients had high rates of unfavorable outcome with 75% at discharge and 58% at 1FU. Likelihood for unfavorable outcome was high in BNI grade 5 patients with OR 5.9 (3.9-8.9) at discharge and OR 6.6 (4.1-10.5) at 1FU. CONCLUSION: This multicenter external validation analysis confirms that patients with a higher BNI grade show a significantly higher risk for DCI; high BNI grade was a predictor for unfavorable outcome at discharge and 1FU.